Thesis and dissertation advising preferences and best practices in the Philippines - Delos Santos, Maria Salud M. (Frontiers in Education, 2025)
This study investigated the advising preferences of graduate students and the best practices of their research advisers in selected private and state universities in Cebu and Palawan. Grounded in the Expectancy-Value Theory, the research examined how students' expectations for success and the value they assign to thesis work influence their advising preferences. A quantitative descriptive survey design was used, involving 72 graduate students enrolled in thesis or dissertation seminars. Data were gathered using a validated instrument (Cronbach's alpha = 0.82) and supplemented by qualitative interviews. Descriptive statistics and thematic analysis were employed. Findings revealed that the top three advising preferences were: (1) coaching and mentoring abilities, (2) field of specialization, and (3) adviser availability. A significant relationship was found between age and advising preference. Thematic analysis yielded three key insights: The Three Cs of Advising, Respect begets Respect, and Have Fun and Enjoy the Journey. The study concludes that understanding and addressing the diverse advising needs of graduate students is essential for creating a supportive academic environment that fosters success and satisfaction. While the findings offer valuable guidance, they are limited by the study's reliance on self-reported data and its specific geographic focus, which may limit broader applicability. The Expectancy-Value Theory provided a useful lens for analysis, though future research may benefit from exploring additional frameworks. The study recommends the development of a thesis and dissertation advising handbook to institutionalize effective advising practices.